Associations of erythrocyte ω‐3 fatty acids with biomarkers of ω‐3 fatty acids and inflammation in breast tissue. Issue 12 (28th July 2015) - Roy, Shuvro; Brasky, Theodore M.; Belury, Martha A.; Krishnan, Shiva; Cole, Rachel M.; Marian, Catalin; Yee, Lisa D.; Llanos, Adana A.; Freudenheim, Jo L.; Shields, Peter G.
<x xml:space="preserve">Abstract</x> There is increasing evidence that chronic inflammation is associated with increased breast cancer risk. Long‐chain omega‐3 polyunsaturated fatty acids (LCω‐3PUFA) may reduce circulating biomarkers of inflammation; however associations of blood LCω‐3PUFA with breast tissue LCω‐3PUFA and breast tissue biomarkers of inflammation are not well understood. We conducted a cross‐sectional analysis of breast tissue and blood samples from n = 85 women with no history of breast cancer, who underwent breast reduction surgery. Fatty acids of erythrocytes and undissected breast tissues were analyzed by gas chromatography; C‐reactive protein (CRP), interleukin (IL)–6 and IL‐8 in plasma and tissue were measured by ELISA. Multivariable‐adjusted regression models were used to estimate associations between erythrocyte LCω‐3PUFA and breast tissue biomarkers. Women in the highest erythrocyte LCω‐3PUFA tertile had LCω‐3PUFA concentrations in the breast 73% (95% CI: 31–128%; p trend < 0.0001) higher than women in the lowest tertile. Associations for each individual LCω‐3PUFA were similar in magnitude. No significant association was found for the shorter ω‐3 PUFA, α‐linolenic acid. Although compatible with no association, women in the highest tertile of erythrocyte eicosapentaenoic acid had a nonsignificant 32% (95% CI: −23 to 62%) reduced breast tissue CRP. No correlation was observed between erythrocyte ω‐3 PUFA and tissue IL‐6 or IL‐8 concentrations. Our findings provide evidence that erythrocyte ω‐3 fatty acids are valid measures of breast tissue concentrations, and limited evidence that inverse associations from prospective epidemiologic studies of blood LCω‐3PUFA and breast cancer risk may be partly explained by reductions in breast tissue inflammation; however, these findings require replication.